2021
DOI: 10.1515/eng-2021-0057
|View full text |Cite
|
Sign up to set email alerts
|

Research on the combustion process in the Fiat 1.3 Multijet engine fueled with rapeseed methyl esters

Abstract: The aim of the paper is to analyze and evaluate the basic parameters of the combustion process in a modern Fiat 1.3 Multijet diesel engine, fuelled esters (FAME) and diesel oil. During the tests on an engine test bed, the pressure waveforms in the cylinder were measured, on the basis of which the averaged actual indicator graphs were established in the determined engine operating conditions. On their basis, the pressure increase rates were determined and heat release characteristics were prepared based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Shortened ignition time registered for with FAME blend obtained between 10 and 60 Nm with 5, 10, and 50% FAME composition. A significantly higher HRRs with p m ax wave recorded between only in the range 10-40 Nm and otherwise the same trend for crank rotation [12].…”
Section: Advanced Technologies and Strategies For Low-temperature Com...supporting
confidence: 59%
See 2 more Smart Citations
“…Shortened ignition time registered for with FAME blend obtained between 10 and 60 Nm with 5, 10, and 50% FAME composition. A significantly higher HRRs with p m ax wave recorded between only in the range 10-40 Nm and otherwise the same trend for crank rotation [12].…”
Section: Advanced Technologies and Strategies For Low-temperature Com...supporting
confidence: 59%
“…The technical report on experimental and analytical evaluation of combustion process parameters on FIAT 1.3 multijet SDE 90 HP engine equipped with Common Rail fuel supply system and electronically controlled solenoid injectors used rapeseed biodiesel or fatty acid methyl ester (FAME) and diesel oil Kierce University of Technology led by Dariusz et al [12] to investigate the maximum combustion phenomena and reported that FAME exhibited slight P max than diesel oil at lower and medium loads despite the superior values at the first two subsequent stages of the maximum combustion [18].…”
Section: Emission Measurement Model Based On Running State and Emissi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of a ramjet engine is shown as figure 7 below. Owing to the removal of moving parts, ramjet engine is considered as the simplest type of jet engine [13]. In addition, the most efficient velocity for the ramjet engine is around 3 Mach, and the maximum velocity is 6 Mach [13].…”
Section: Ramjet Engine and Scramjet Enginementioning
confidence: 99%
“…Owing to the removal of moving parts, ramjet engine is considered as the simplest type of jet engine [13]. In addition, the most efficient velocity for the ramjet engine is around 3 Mach, and the maximum velocity is 6 Mach [13]. However, it is impossible for a ramjet engine operate independently because of disappearing compressor and turbine [12].…”
Section: Ramjet Engine and Scramjet Enginementioning
confidence: 99%